What is social capital? A comprehensive review of the concept - Bhandari, Humnath; Yasunobu, Kumi (Elsevier, 2009)
Social capital is an old concept but it entered into academic and policy debates only in 1990s. Its importance in explaining economic and social phenomena have been increasingly felt in recent years. Literature on theoretical and empirical aspects of social capital grew significantly during last decade. The whole notion of social capital is centred on social relationships and its major elements include social networks, civic engagement, norms of reciprocity, and generalised trust. Broadly speaking, it is defined as a collective asset in the form of shared norms, values, beliefs, trust, networks, social relations, and institutions that facilitate cooperation and collective action for mutual benefits. It is a complex multidimensional concept having different dimensions, types, and levels of measurement. Common types of social capital include: structure and cognitive; bonding, bridging, and linking; strong and weak; and horizontal and vertical. It can be measured and analysed at individual- and collective-levels in terms of social perspective and micro-, meso- and macro-levels in terms of geographic perspective. The properties of social capital, such as capacity to appear in as an explanatory variable in the production function, accumulation over time, capability of improving economic performance, investment with expected future returns, convertibility, and the need of maintenance, make it qualify as a form of capital, though there are some criticisms about the use of term 'capital' in social capital. Research on social capital remains in its initial stage and the concept is still elusive, prone to contextual definition, deficient in common measurement indicators, inability to explicitly quantify effects, and subject to various criticisms. Conceptual and measurement imprecision has led the concept prone to vague interpretation, less empirical application, and underestimation of its value. More empirical studies and testing of the concept on the ground is needed to develop a commonly accepted definition and measurement indicators that can explicitly disentangle and quantify its effects on overall development processes. Better conceptualisation and operationalisation of social capital theory is helpful to attract more investment on its development, design appropriate social policies, and promote sustainable development.